2018
DOI: 10.1002/14651858.cd011517.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mesh versus non-mesh for inguinal and femoral hernia repair

Abstract: Mesh and non-mesh repairs are effective surgical approaches in treating hernias, each demonstrating benefits in different areas. Compared to non-mesh repairs, mesh repairs probably reduce the rate of hernia recurrence, and reduce visceral or neurovascular injuries, making mesh repair a common repair approach. Mesh repairs may result in a reduced length of hospital stay and time to return to activities of daily living, but these results are uncertain due to variation in the results of the studies. Non-mesh repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 72 publications
0
86
0
4
Order By: Relevance
“…On one hand, compared to nonmesh repairs, mesh repairs reduce the rate of hernia recurrence and involve a shorter operation time and faster return to normal activities. On the other hand, testicular complications probably occur slightly more often in mesh repairs and show nearly equivocal results 12 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…On one hand, compared to nonmesh repairs, mesh repairs reduce the rate of hernia recurrence and involve a shorter operation time and faster return to normal activities. On the other hand, testicular complications probably occur slightly more often in mesh repairs and show nearly equivocal results 12 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…For example, Mitura et al showed that there are anatomical differences in the inguinal region between Africans and Caucasians and that therefore pure tissue repairs could be promising, especially for African patients [24]. A recent Cochrane analysis also recommends mesh-free methods for LICs [25].…”
Section: Discussionmentioning
confidence: 99%
“…Многолетнее использование сетчатых протезов не выя-вило доказательств канцерогенного потенциала грыжевых сеток [90]. Вместе с тем, использование протезирующих технологий в 2-4% осложняется развитием хирургической раневой инфекции и в 15% -хроническими болями [91][92][93][94][95]. Видеоэндоскопические операции сократили сроки пребывания больных в стационаре до суток.…”
Section: обзорные статьи Vol 4 № 3 2019 ®unclassified